Doukanari, Marina - (:unkn) unknown (My University, 2026)
Marina Doukanari holds a Master of Science degree from the Interdepartmental Program in Conservation and Restoration of Historical Buildings and Monuments from the University of Cyprus and a Bachelor of Science degree in Land Surveying and Geoinformatics Engineering from the Cyprus University of Technology. She is currently serving as a Research Assistant A' at the Eratosthenes Centre of Excellence in the Department of Big Earth Data Analytics (Geo-Informatics). Since 2017, Marina has contributed to various projects in the construction industry, including overseeing construction works, conducting quantity surveying, and generating as-built drawings for large-scale, EU-funded projects. Her broad expertise encompasses cadastral work, land measurements, road works, plot divisions and consultations with relevant authorities, among others. She has held positions as a Technical Engineer at both Nicosia’s Department of Lands and Surveys and the District Administration Office of Larnaca. In 2016, she was an intern at Marathon Data Systems in Athens, focusing on the ArcGIS platform, while enhancing her skills as a G.I.S. Analyst. Marina’s collaborative work with archaeologists and architects underscores her specialization in historical monuments. Additionally, she is a registered Authorized Private Surveyor in Cyprus, a member of the Cyprus Scientific and Technical Chamber (ETEK), and a member of ICOMOS USA.